#### Answer

a: -7/2
b: -5
c: 11/5

#### Work Step by Step

a: $\frac{2(-1)^3-5}{(-1)^2+1} = \frac{-2-5}{1+1} = -\frac{7}{2}$
b: $\frac{2(0)^3-5}{(0)^2+1} = \frac{-5}{1} = -5$
c: $\frac{2(2)^3-5}{(2)^2+1} = \frac{2(8)-5}{4+1} = \frac{11}{5}$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

a: -7/2
b: -5
c: 11/5

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.